Kajian Kesesuaian Lahan Ekowisata Mangrove Di Desa Arakan Kabupaten Minahasa Selatan Sulawesi Utara - Angelitha O.T Iskandar; Joshian N.W Schaduw; Natalie D.C Rumampuk; Calvyn F.A Sondak; Veibe Warouw; Ari Rondonuwu (Sam Ratulangi University, 2019)
Study Of Land Suitability For Mangrove Ecotourism In Arakan Village, Minahasa Selatan District, North Sulawesi The purpose of this study was to determine community structure, mangrove canopy cover and land suitability of mangrove ecotourism. This study used the line transect method for mangrove community structure, interviews for questionnaires and hemispherical photography for the percentage of mangrove cover. The results of the study on mangrove community structure showed that The highest important value index is found in transect 3, namely R. stylosa with value of 292,935 and the lowest on transect 3 is A. officinalis with a value of 7.065. For the suitability of mangrove ecotourism land shows that all transects belong to the suitable category with value of 55.74% on transect 1, 65.57% on transect 2, 68.85% on transect 3, 63.93% on transect 4 and 68.85% on transect 5.Keywords: Mangrove, Ecotourism, Arakan VillageÂ Tujuan dari penelitian ini adalah untuk mengetahui struktur komunitas, tutupan kanopi mangrove dan kesesuaian lahan ekowisata mangrove. Penelitian ini menggunakan metode line transek terhadap struktur komunitas mangrove, wawancara untuk kuisioner dan hemispherical photography untuk persentase tutupan mangrove. Hasil penelitian struktur komunitas mangrove yaitu indeks nilai penting tertinggi terdapat pada transek 3 jenis R.stylosa 292.935 dan terendah pada transek 3 jenis A.officinalis 7.065. Untuk kesesuaian lahan ekowisata mangrove bahwa pada semua transek masuk kategori sesuai dengan nilai kesesuaian transek 1 55.74%, transek 2 nilai 65.57%, transek 3 nilai 68.85%, transek 4 nilai 63.93% dan transek 5 nilai 68.85%.Kata kunci: Mangrove, Ekowisata, Desa Arakan.